Fecal Microbiota Transplantation for Weight and Glycemic Control of Obesity as Well as the Associated Metabolic Diseases: Meta-Analysis and Comprehensive Assessment - Diangeng Hu; Jianxin Zhao; Hao Zhang; Gang Wang; Zhennan Gu (Life, 2023)
Objectives: An analysis of the weight and blood glucose management associated with fecal microbiota transplantation (FMT) as well as metabolic diseases associated with FMT was conducted by the authors in order to provide clinical recommendations regarding the treatment of nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM). Methods: We searched PubMed, Embase, and the Cochrane Library for papers that were published between the creation of the database and October 2022. We reviewed research that investigated how FMT affected weight and glycemic management in cases of obesity and metabolic conditions that are related to obesity. Studies that were published more than once, lacked the entire text, included insufficient information, or were impossible to extract data from were excluded. Additionally, case reports, reviews, and systematic reviews were excluded from the analysis. In order to analyze the data, STATA 15.1 was used. Outcomes: When we combined all of our findings, we discovered that pooled outcomes showed that weight levels (WMD equals −4.77, 95%CI: −7.40~−2.14), BMI levels (WMD equals −1.59, 95%CI: −2.21~−0.97), HOMA-IR (WMD equals −0.79, 95%CI: −1.57~−0.00), and HbA1c (WMD equals −0.65, 95%CI: −0.75~−0.55) after FMT treatment were significantly lower than before treatment. However, FMT treatment may have no effect on glucose and insulin levels in obese patients at fasting and related metabolic diseases. Additionally, subgroup analysis outcomes found that FMT significantly reduced fasting blood glucose in people with diabetes. Conclusions: As a weight loss and glycemic control therapy, FMT helps to prevent and treat metabolic problems linked to obesity, and is a viable alternative to bariatric surgery for patients who do not wish to undergo the procedure.